An Implementation Review of The Program of Complete Systematic Land Registration In Indonesia - Arief Maulana; Chumanidya Utami; Yana Suryana (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
Complete Systematic Land Registration (PTSL) is the process of registering land for the first time, which is carried out simultaneously and includes all objects of land registration that have not been registered in an area. Through this program, the government guarantees legal certainty or rights to land owned by the community. However, the importance of land registration in Indonesia has not been followed by a good understanding by the community. Many lands in Indonesia that have not been certified are due to various factors that prevent communities from registering ownership rights to their land. This study aims to describe the implementation of the PTSL program and analyze the program related to its role in resolving land disputes in Indonesia. This study is qualitative research and used an interpretive paradigm. Data collection techniques were carried out through literature studies and focus group discussions. The results showed that PTSL is not a form of agrarian reform at the implementation level. The PTSL program still has things that have the potential to become problems in the future, including the implementation of PTSL is still fertile with the practice of extortion, potential claims on land after certification are still often occurred, and the non-functioning of the publicity and delimitation contradictory principle has resulted in many land conflicts/disputes.